Crisis Management Strategy for Obstacles in Issuing Transit Visas for the Saudi Arabian International Community Service Program at UIN Walisongo Semarang in 2025 - Muhammad Izzudin Karim; Kurnia Muhajarah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The implementation of pre-departure crisis management is a crucial aspect in the implementation of the International Community Service Program (KKN). This study aims to analyze the effectiveness of the crisis management strategy implemented by UIN Walisongo Semarang in addressing the obstacles in issuing transit visas for Saudi Arabian students participating in the International KKN program, and to formulate practical solutions as recommendations for the institution. This study uses a qualitative method with a descriptive case study approach, involving in-depth interviews with the KKN organizing committee, travel agents, and affected participants. Data collection techniques include observation, interviews, and documentation. The results show that the pre-crisis phase experienced significant failures due to the lack of updated information on the United Arab Emirates (UAE) transit visa regulations by the Tour Leader and the underestimation of visa processing time. Nevertheless, crisis management strategies during the crisis phase (crisis event), such as problem-focus and adaptive coping, successfully minimized the impact of losses. These findings emphasize the urgency of crisis management and effective strategies in international KKN. This study presents an in-depth analysis of transit visa crisis management, which has rarely been studied, particularly in the context of the Hajj and Umrah Management program at UIN Walisongo Semarang.